2022
DOI: 10.21203/rs.3.rs-1444367/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theaflavin 3-gallate inhibits the main protease (Mpro) of SARS-CoV-2 and reduces its count in vitro

Abstract: Main protease (Mpro) of SARS-CoV-2 is crucial for its replication/infection and has been recognized as an attractive drug target. In this study, we identified theaflavin 3-gallate as an inhibitor of Mpro protein of SARS-CoV-2 with IC50 value of 18.48 ± 1.29 µM. Compared to theaflavin, theaflavin 3-gallate exhibited superior antiviral activity and at a concentration of 200 µM reduced the viral count by 75% (viral particles reduced from 106.7 to 106.1). Time-dependent analyses of conventional and steered MD-simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Moreover, MD simulations analyses indicated that TF2 has stronger interactions with the active site of Mpro compared to TF. Also, TF2 formed a higher number of H‐bonds throughout the entire simulation run and showed a low binding energy of −48.02 kcal/ mol, compared to TF (−11.21 kcal/mol) (Chauhan et al, 2022).…”
Section: Search For Natural Antiviral Agents Against Sars‐cov‐2mentioning
confidence: 99%
“…Moreover, MD simulations analyses indicated that TF2 has stronger interactions with the active site of Mpro compared to TF. Also, TF2 formed a higher number of H‐bonds throughout the entire simulation run and showed a low binding energy of −48.02 kcal/ mol, compared to TF (−11.21 kcal/mol) (Chauhan et al, 2022).…”
Section: Search For Natural Antiviral Agents Against Sars‐cov‐2mentioning
confidence: 99%
“…To date, a large amount of experimental [17] , [18] , [19] , [20] , [21] , [22] , [23] and theoretical studies [24] , [25] , [26] , [27] , [28] have been conducted elucidating the structure of the SARS-CoV-2. There are also a wide variety of studies showing that the spike [29] , [30] , [31] , [32] , [33] , [34] , the main protease [35] , [36] , [37] , [38] , the RNA-dependent RNA-Polymerase [39] , [40] and some other non-structural proteins such as protein 1 [41] , protein 15 [42] and protein 16 [43] can be potential targets in the development of therapeutic drugs and the design of vaccines to fight this virus [44] , [45] , [46] , [47] .…”
Section: Introductionmentioning
confidence: 99%